Turning-Off Signaling by Siglecs, Selectins, and Galectins: Chemical Inhibition of Glycan-Dependent Interactions in Cancer - Cagnoni, Alejandro J.; Pérez Sáez, Juan M.; Rabinovich, Gabriel A.; Mariño, Karina V. (Frontiers in Oncology, 2016)
Aberrant glycosylation, a common feature associated with malignancy, has been implicated in important events during cancer progression. Our understanding of the role of glycans in cancer has grown exponentially in the last few years, concurrent with important advances in glycomics and glycoproteomic technologies, paving the way for the validation of a number of glycan structures as potential glycobiomarkers. However, the molecular bases underlying cancer-associated glycan modifications are still far from understood. Glycans exhibit a natural heterogeneity, crucial for their diverse functional roles as specific carriers of biologically-relevant information. This information is decoded by families of proteins named lectins, including siglecs, C-type lectin receptors (CLRs) and galectins. Siglecs, sialic-acid binding transmembrane lectins, are primarily expressed on the surface of immune cells and differentially control innate and adaptive immune responses. Among CLRs, selectins are a family of cell adhesion molecules that mediate interactions between cancer cells and platelets, leukocytes and endothelial cells, thus facilitating tumor cell invasion and metastasis. Galectins, a family of soluble proteins that bind β-galactoside-containing glycans, have been implicated in diverse events associated with cancer biology such as apoptosis, homotypic cell aggregation, angiogenesis, cell migration and tumor-immune escape. Consequently, individual members of these lectin families have become promising targets for the design of novel anticancer therapies. During the past decade a number of inhibitors of lectin-glycan interactions have been developed including small-molecule inhibitors, multivalent saccharide ligands, and more recently peptides and peptidomimetics have offered alternatives for tackling tumor progression. In this article, we review the current status of the discovery and development of chemical lectin inhibitors and discuss novel strategies to limit cancer progression by targeting lectin-glycan interactions.